2004
DOI: 10.1172/jci200422220
|View full text |Cite
|
Sign up to set email alerts
|

Atrogin-1/muscle atrophy F-box inhibits calcineurin-dependent cardiac hypertrophy by participating in an SCF ubiquitin ligase complex

Abstract: Calcineurin, which binds to the Z-disc in cardiomyocytes via α-actinin, promotes cardiac hypertrophy in response to numerous pathologic stimuli. However, the endogenous mechanisms regulating calcineurin activity in cardiac muscle are not well understood. We demonstrate that a muscle-specific F-box protein called atrogin-1, or muscle atrophy F-box, directly interacts with calcineurin A and α-actinin-2 at the Z-disc of cardiomyocytes. Atrogin-1 associates with Skp1, Cul1, and Roc1 to assemble an SCF atrogin-1 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
343
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(374 citation statements)
references
References 54 publications
15
343
0
Order By: Relevance
“…Previous studies showed FoxO1 and FoxO3 can promote expression of the atrophy-associated ubiquitin ligase gene atrogin-1, and Atrogin-1 can also activate FoxO1 function in cardiomyocyte cell cycle control (26,33,59). Similarly in skeletal muscle, FoxO3 induces both atrophy and autophagy, leading to decreased cell size through direct regulation of atrophy and autophagy-associated genes (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed FoxO1 and FoxO3 can promote expression of the atrophy-associated ubiquitin ligase gene atrogin-1, and Atrogin-1 can also activate FoxO1 function in cardiomyocyte cell cycle control (26,33,59). Similarly in skeletal muscle, FoxO3 induces both atrophy and autophagy, leading to decreased cell size through direct regulation of atrophy and autophagy-associated genes (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of these studies is problematic, however, because cyclosporin A mediates calcineurin-independent effects, and MCIP has dual effects on calcineurin activity (37)(38)(39). In a recent study (40), the F-box adapter protein atrogin-1 was identified as a unique binding partner of calcineurin and ␣-actinin at the Z-disk. In the face of hemodynamic stress, atrogin-1 promotes ubiquitin-dependent degradation of calcineurin, resulting in a reduced hypertrophic response (less cardiomyocyte thickening), enhanced cardiac dilation, and enhanced ventricular dysfunction (40).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study (40), the F-box adapter protein atrogin-1 was identified as a unique binding partner of calcineurin and ␣-actinin at the Z-disk. In the face of hemodynamic stress, atrogin-1 promotes ubiquitin-dependent degradation of calcineurin, resulting in a reduced hypertrophic response (less cardiomyocyte thickening), enhanced cardiac dilation, and enhanced ventricular dysfunction (40). These data are very much reminiscent of our findings that impaired MLP-calcineurin signaling at the Z-disk is associated with blunted transverse myocyte growth, more pronounced ventricular dilation, and contractile dysfunction (i.e., adverse remodeling).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative PCR primers for ANF, brain natriuretic factor, b-myosin heavy chain and GAPDH were as described earlier. 23 …”
Section: Real-time Quantitative Pcr Analysismentioning
confidence: 99%